Sport psychology essentials - Collins, Dave PhD; Cruickshank, Andrew PhD (Human Kinetics, Inc., 2023)
This comprehensive look at sport psychology presents current research-based information and applied techniques to benefit coaches, athletes, performance specialists, and sport psychology consultants. Topics include making sport psychology work, strengthening athletes' performance mindset, and enhancing team performance potential. Special emphasis is placed on developing confidence, increasing motivation, and preparing individuals and teams for optimal performance